Artificial Intelligence And Service Flexibility In Healthcare: Exploring the Nexus - Pradeep Kumar (ACHSM, 2024)
Artificial Intelligence (AI) has the potential to revolutionize healthcare by enabling the development of more personalized, efficient, and effective medical services. One aspect of AI competence in healthcare that has received significant attention is the ability to respond rapidly to the patients' dynamic needs while injecting more flexibility into the system. This research explores the nexus between AI and service flexibility in healthcare. The qualitative study was carried out to examine the flexibility perspectives of AI-enabled service deliveries in healthcare. The findings contribute to a nuanced understanding of the facets of service flexibility in healthcare that AI could enable. The results would guide better coordination and management of care and the ability to make more informed decisions about treatment options. The nexus between AI and service flexibility in healthcare would sketch the new paradigms of patient value creation and evidence-based practices, which is an immediate need of healthcare organizations across the globe.